Instructional time impact at an EFL content area course for a student with learning disablities from Unidad Educativa Particular Americus Mundus Novus. - Arias Armijo, Ammy Annabel (2018)
This study is about an inclusion student from Unidad Educativa Particular Americus Mundus Novus and her relation with her physics and chemistry English classes. This student presents cognitive and social disabilities. To start the study, theories were researched regarding the topics on learning disabilities, the role of the teacher’s inside an EFL class, and the responsibility that the school has. Taking into account the diagnostic test, and its results, instruments were designed in order to gather the information from the inclusion student and the environment around her; the results showed the key factors that influenced her performance in class and outside the class. A quasiexperiment was employed to measure the time-on-task and a mixed methods analysis was developed. After the analysis was done, the results achieved from this experiment showed that the student is not being adequately addressed due to the lack of instructional time. The student has not reached the level needed for this content area course; the short class sessions demonstrate that she is having difficulties in class: feeling uncomfortable or not really working with the rest of the classmates which indicate that peer work or team work will not help her to progress inside the class. Thus, a proposal was designed to reach the goal wanted with the inclusion student.